A study on job satisfaction among firemen of Fire and Rescue Department of Jalan Kubu, Melaka / Amru Tajul Arifin - Tajul Arifin, Amru (Faculty of Administrative Science and Policy Studies, 2013)
Job satisfaction among the employees has a great impact towards an organization as there is correlation with employee’s performance, absenteeism and turnover. Many organizations were concerned about measuring the job satisfaction among their workers (Carsten & Spector, 1987). Job satisfaction can be related to factors which could either motivate or demotivate the employees (Herzberg, 1968; Herzberg, Mausner, & Snyderman, 1959). Job satisfaction is important because a person's attitude and beliefs may affect his or her behavior in the workplace. Attitudes and beliefs may cause a person to work harder or the opposite may occur and he or she may work less. Job satisfaction also affects a person's general well-being as people spend a great part of their day at work. If a person is dissatisfied with their work, it could lead to dissatisfaction in other areas of their life (Jex, 2002).